THE IMPORTANCE OF EXPLORING IN ENTREPRENEURSHIP LEARNING FOR EARLY CHILDHOOD (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
Education that is happening now is experiencing rapid changes and developments from year to year. Change occurs because it follows the development of the current era. For this reason students must be equipped with the skills that must be possessed to be able to deal with the changing times. Education must also have an interesting learning method to prepare 21st century special children. Learning entrepreneurship has the principle that learning must be student-centered, collaborative, contextual, and integrated with society. The skill that is most needed in the century of entrepreneurship learning is the skill to explore , where children are asked to explore their surroundings to become a learning material both through books, the internet, and from the surrounding environment. By exploring students will get a lot of knowledge even students will get an opportunity in creating an interesting innovation. For early childhood education, developing skills to explore, students must be guided by the teacher. The teacher has a very strong role to foster an attitude of exploration for children. For this reason the teacher must have an exploration need when doing learning in the classroom. The role of the teacher in carrying out 21st century learning is very important in realizing a better future for the nation.